Organization Of Monitoring The Quality Of Services Provided To Prevent And Combat Postpartum Bleeding In Women (Texas Journal of Medical Science, 2026)
This article describes how to monitor the quality of care for women during pregnancy and childbirth for postpartum haemorrhage, evaluate the clinical and cost-effectiveness of care, standard requirements, and conduct surveys, patient reviews and prioritize complaints and appeals. . feedback on patient satisfaction monitoring